Amyloids facilitate DNA transfection in vivo. (July 2022) - Imamura, Yukio; Hiyama, Akiko; Miyazaki, Haruko; Yamanaka, Tomoyuki; Nukina, Nobuyuki
Abstract: Amyloid fibril deposits are a main source of pathology in neurodegenerative diseases. Normal proteins such as tau, alpha-synuclein, TDP-43 and others could form specific conformational fibrils called amyloid, which deposited in the brains of neurodegenerative diseases. Although the pathological roles of amyloids in cell death have been discussed a lot, their other functions have not been investigated well. Here, we studied the effect of amyloids on DNA transfection in vivo. We injected quantum dot labeled or non-labeled amyloid-preformed fibrils (PFFs) and a green fluorescent protein (EGFP) expression vector into organs including brain, testis, liver and calf muscle. GFP expression patterns were examined by immunohistochemistry and western blotting. At 24 h after injection, EGFP was predominantly expressed in the neurons in the cortex and the striatum, Leydig cells in testis, hepatocytes in the liver and muscle cells. EGFP expression was inhibited by an endocytosis inhibitor, sertraline in the brain and testis. The amyloid-PFFs potentiated Ca 2+ transients shown by calcium imaging and EGFP expression in the brain was blocked by Ca blocker, cilnidipine. Our results show that amyloid-PFFs facilitate DNA transfection and can be used for a new gene delivery system in vivo. Highlights: Amyloid-PFFs facilitates DNA transfection in the brain, testis, liver and calf muscle. Amyloid-PFFs induced transfection is endocytosis dependent. Amyloid-PFFs induced transfection in the brain is calcium and neuronal activity dependent.